Integrated Crop Management in Niger for Higher Productivity in Hill and Tribal Areas of Andhra Pradesh, India - , G. Chitti Babu; , P. Venkata Rao; , P B Pradeep Kumar; , J Jagannadham (Archives of Current Research International, 2024)
Niger crop is being cultivated in hilly and tribal agency Mandals of Alluri Sitarama Raju district in Andhra Pradesh in an area of 3900 ha during late kharif. Though Niger is an economically potential crop, non-adoption of scientific recommendations by the farmers leading to reduced or poor yields, 400-450kg/ha. District Agricultural Advisory and Transfer of Technology Centre (DAATTC), ASR District has conducted demonstrations in the selected tribal Mandals on Integrated Crop Management (ICM) in Niger for higher productivity for the benefit of farming community during 2023. ICM demonstrated plots has recorded improved yields (562 kg/ha) compared to the farmers practice (458 kg/ha) in the ASR District. The productivity of Niger crop was improved upto 22.7 per cent in the ICM demonstrated plots and the BC ratio recorded was 1: 4.80 as against 1:3.95. Also educated the farmers through the awareness programmes on crop management and most of the farmers were convinced with the results in integrated crop management practices in Niger.